Study of Placental Pathology in Cases of Intrauterine Fetal Deaths - Borade, Pramod Dharmraj; Kanetkar, Sujata R; Kale, Pradnya Pandurang; Hulwan, Atul Bhanudas; Shukla, Dhirajkumar B; Vohra, Nikita Vinod (Annals of Pathology and Laboratory Medicine, 2018)
Background: Intrauterine fetal death is agonizing, often unpredictable event. The mother, the fetus, and the placenta all are involved in the complex process of fetal death and therefore, should be addressed together. Unfortunately, the cause of death is unexplained sometimes up to two third of intrauterine deaths. For the proper determination of the cause, and further prevention, Placenta is the most accessible and readily evaluable specimen which is mirror image of pregnancy. Methods: This cross-sectional study was carried out in the Department of Pathology in a tertiary care hospital from June 2015 to May 2017. Material for the present study comprised of 99 placentas obtained from the cases of IUFD, delivered in the Department of Obstetrics and Gynecology of a tertiary care hospital. These 99 placentas were received in the Department of Pathology along with clinical details for histomorphological study. Result: Histopathological examination of placenta revealed following findings - Perivillous fibrin 62/99 (62.62%) cases, calcification 51/99 (51.51%) cases, intervillous hemorrhage 46/99 (46.46%) cases, prominent syncytial knots 45/99 (45.45%) cases, cytotrophoblastic proliferation 41/99 (41.41%) cases, increased vascularity 31/99 (31.31%) cases, fibrinoid necrosis 19/99 (19.19%) cases, hydropic villi 09/99 (09.09%) cases and villitis in 07/99 (07.07%) cases. Conclusion: The placenta can be considered as the diary of pregnancy. After fetal death, it remains viable for several days. The value of examining the placenta determining cause of death in intrauterine fetal death is evident and varies from 28-85%.The value depends largely on the quality of the placental reports.